ANALISIS STRATEGI PEMASARAN PADA KEDAI PERSEPHONE COFFE MENGGUNAKAN METODE SWOT DAN QSPM - Ihwan Nudin, Mohammad Rizky; Suryaningprang, Andre (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the marketing strategy of Persephone Coffee Shop using the SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) methods. These approaches are applied to identify the shop’s strategic position and prioritize marketing strategies to enhance competitiveness and business performance. Data were collected through interviews, observations, and relevant document reviews. The SWOT analysis revealed strengths such as product quality and strategic location, weaknesses such as limited promotion, opportunities like the growing coffee consumption trend, and threats from intense market competition. The QSPM analysis indicated that the priority strategy is to enhance digital marketing and expand market reach through collaborations with local communities. This study provides recommendations for implementing marketing strategies based on systematic analysis, thereby aiding Persephone Coffee Shop in boosting competitiveness and growth in the coffee industry.